ADMINISTRATION SYSTEM FOR BOOKING ROOMS IN HOTEL "XYZ" USING VISUAL BASIC 6.0 - Ardiansyah Ardiansyah; Aqwam Rosadi Kardian, SKom., MM. (Jurnal Sistem Informasi, 2005)
The development of increasingly sophisticated computer that is very helpful in dataprocessing still using manual systems. This often raises issues related to the accuracyof the data which resulted in delays in the process of service at the hotel. In thiscontext, the authors are interested in creating an application program design acomputerized hotel reservation. In this penulissan section discusses the process ofservice the hotel front office "XYZ", Data Flow Diagrams (DFD), Entity RelationshipDiagram (ERD), Normalization, and view Microsoft Visual Basic 6.0 program.